Axial compressive behaviour of circular concrete-filled steel tubular stub columns with an inner bamboo culm. (August 2020) - Gan, Dan; Li, Zexiang; Zhang, Tao; Zhou, Xuhong; Chung, Kwok-fai
Abstract: Circular concrete-filled steel tubular columns (CFST) with an inner bamboo culm, by replacing the internal steel tube of concrete-filled double skin steel tubular (CFDST) columns with a structural bamboo culm, promote the use of natural materials with lower cost and lighter weight. This type of composite column is expected to integrate the advantages of all the three kinds of materials. Twenty-two circular stub columns including 12 CFST with an inner bamboo culm, 3 CFST columns, 4 CFDST columns and 3 hollow CFST columns were tested under axial compression. The test parameters include the bamboo culm thickness, the bamboo culm diameter and the diameter to thickness ratio of the external steel tubes. Test results indicated that the columns with an inner bamboo culm had excellent ductility. Furthermore, the columns with an inner bamboo culm showed strain-hardening behaviour after an initial decline in its axial load-displacement curve, but the inner bamboo culm contributed mildly to the ultimate load. Finally, a unified formula was proposed to predict the load-carrying capacities of all the four types of composite columns.